The Effect Of Motivation, Leadership And Organizational Culture On Employee Performance In Pt Buana Wirasubur Sakti - Yovie Ernanda; Felica Potami; Sakinah Lubis; Yuliani (International Journal of Science, Technology & Management, 2021)
This study aims to determine the effect of motivation on employee performance at PT. Buana Wirasubur Sakti, to determine the influence of leadership on employee performance at T. Buana Wirasubur Sakti, to determine the influence of organizational culture on employee performance at PT. Buana Wirasubur Sakti, to determine the effect of motivation, leadership and organizational culture on employee performance at pt. the world of wirasubur magic. The population in this study are all employees of PT. Buana Wirasubur Sakti numbered 75 people with a saturated sampling technique using total sampling obtained a research sample of 75 people.The results showed that partially and simultaneously motivation, leadership and organizational culture had a positive and significant effect on the performance of PT. Buana Wirasubur Sakti. The results of the regression calculation can be seen that the coefficient of determination (R square) obtained is 0.492, this result means that 49.2% of employee performance variables can be explained by motivation, leadership, organizational culture variables, while the remaining 50.8% is explained by other variables not examined.